O-027 The INVEST Trial: A Randomized, Controlled Trial to Investigate the Safety and Efficacy of Image Guided Minimally Invasive Endoscopic Surgery with Apollo vs Best Medical Management for Supratentorial Intracerebral Hemorrhage. (29th July 2016) - Fiorella, D; Arthur, A; Mocco, J
Abstract : Introduction: Spontaneous intracerebral hemorrhage (ICH) is a common subtype of hemorrhagic stroke, and has the poorest prognosis amongst all stroke subtypes. The goal of the INVEST trial, as well the parallel European EPOCH trial, is to evaluate the safety and efficacy of the minimally invasive hemorrhage evacuation with Apollo device (Penumbra Inc, Alameda, CA) compared to medical management. Methods: The INVEST study is a prospective multicenter US trial designed to enroll 222 patients at up to 30 centers. The parallel European EPOCH study is a 240 patient, 40 center RCT. Patients between the ages of 22–80 or <85 with baseline mRS = 0 or 1, NIHSS of at least 6, and presenting with a moderate to large volume supratentorial ICH (30–80 cc) within 24 h of onset are eligible for enrollment. Qualifying patients will be randomized (1:1) to either minimally invasive surgery (MIS) with Apollo or to the best medical management (MM). Follow up for each patient will be conducted at days 3, 7, discharge, 30, 90, 180, and 360 from enrollment. The primary endpoints are mRS ≤ 3 at 180 days and mortality at 30 days. Secondary endpoints include stroke impact scale (SIS)-mobility, SIS-ADLs and EQ-5D-5L at 180 days, and length of hospitalization. All imaging will be assessed by an independent core laboratory. Results: Centers are currently in the process of initiation with a potential start date of forthcoming. Updated data on trial progress will be discussed at the time of presentation. Conclusion: The INVEST and EPOCH studies are designed to provide an assessment of the safety and efficacy of Apollo MIS for the treatment of spontaneous supratentorial ICH. The parallel structure of the two trials presents a potential for a pooled statistical analysis provided the data are sufficiently homogenous. Disclosures: D. Fiorella: 1; C; Sequent Medical, Penumbra, Microvention, Seimens. 2; C; Sequent, Microvention, Medtronic, Penumbra, Codman. A. Arthur: 1; C; Penumbra. 2; C; Penumbra, Stryker. J. Mocco: 1; C; Penumbra. 2; C; Lazurus Effect, Reverse Medical, Pulsar, Edge Therapeutics, Medina Medical. 4; C; Blockade Medical, Lazurus Effect.